2020
DOI: 10.1007/s11414-020-09716-2
|View full text |Cite
|
Sign up to set email alerts
|

Our Voice and Our Vote Are More Important Than Ever Before

Abstract: The COVID-19 pandemic has made it clear how vital behavioral health professionals are to our individual health and to the health of our communities. More than ever, behavioral health professionals provide clients with life-saving treatment and services. It is truly hard to imagine where we would be as a nation without care from behavioral health professionals. The need will only intensify in the weeks and months ahead as we face a long period of recovery of our health, spirit, and economy, addressing the inevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It becomes apparent that communitywide approaches which will focus on social integration and behavioral support, beyond communication and education about the virus, are needed for subgroups of the Greek population who are on the fence of social isolation. 41 We also found that increased exposure to COVID-19 related Media news and online resources was associated with more frequent engagement in mask-wearing and hand washing. The transparency and openness of the Greek government with daily updates on the virus' spread in the country followed by public health messaging, guidelines and recommendations for prevention appears to be key in the public's acceptance of preventive measures.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It becomes apparent that communitywide approaches which will focus on social integration and behavioral support, beyond communication and education about the virus, are needed for subgroups of the Greek population who are on the fence of social isolation. 41 We also found that increased exposure to COVID-19 related Media news and online resources was associated with more frequent engagement in mask-wearing and hand washing. The transparency and openness of the Greek government with daily updates on the virus' spread in the country followed by public health messaging, guidelines and recommendations for prevention appears to be key in the public's acceptance of preventive measures.…”
Section: Discussionmentioning
confidence: 52%
“…It becomes apparent that community-wide approaches which will focus on social integration and behavioral support, beyond communication and education about the virus, are needed for subgroups of the Greek population who are on the fence of social isolation. 41 …”
Section: Discussionmentioning
confidence: 99%